Exercise is the Foundation of Weight Loss - WANG Qianqian, WANG Xiaohang, ZHOU Xiaoying, QIU Shanhu, SUN Zilin (Zhongguo quanke yixue, 2023)
The prevalence of overweight and obesity has been increasing yearly and become a global public health problem with a range of consequences causing widespread concern. Weight loss can reduce the incidence of type 2 diabetes, cardiovascular risk, and all-cause mortality. The most common approaches of weight loss are drug therapy, surgery and lifestyle interventions including diet and exercise, however, exercise intervention remains the healthiest and most fundamental approach of weight loss. Exercise can reduce cellulite, increase muscle mass and improve metabolism. The combination of exercise and other weight loss approaches can reduce adverse reactions and produce better results. Continuing exercise after weight loss can also effectively prevent rebound and maintain weight loss effects. This paper reviews the definition, mechanism, effect, and management of "exercise is the foundation of weight loss", and provide a reference for weight loss through exercise in the context of the experience of Zhongda Hospital.